2014
DOI: 10.1089/jop.2013.0231
|View full text |Cite
|
Sign up to set email alerts
|

Penetration Force, Geometry, and Cutting Profile of the Novel and Old Ozurdex Needle: The MONO Study

Abstract: On behalf of the German Retinal Vein Occlusion GroupAbstract Purpose: To investigate the geometry, penetration force, and cutting profile of the novel and old needle of the drug delivery system (DDS) for Ozurdex injections in a standardized laboratory setting. Methods: In this experimental study, the normative geometrical data of the DDS needle were systematically analyzed according to nomenclature DIN 13097 (ISO 7864) and ISO 9626. The force to penetrate a standardized 0.4-mm-thick polyurethane foil was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Meyer et al compared the geometry, penetration force and cutting profile of the novel and standard needles of the drug delivery system for injections of a dexamethasone-containing implant (DEX-implant; OZURDEX, Allergan, Inc., Irvine, CA, USA). 39 The study concluded that enhanced geometry of the needle tip could significantly improve the cutting profile through reduced penetration forces in experimental conditions. Hence, the IVI of the OZURDEX implant in humans could be performed in a smoother manner.…”
Section: Discussionmentioning
confidence: 97%
“…Meyer et al compared the geometry, penetration force and cutting profile of the novel and standard needles of the drug delivery system for injections of a dexamethasone-containing implant (DEX-implant; OZURDEX, Allergan, Inc., Irvine, CA, USA). 39 The study concluded that enhanced geometry of the needle tip could significantly improve the cutting profile through reduced penetration forces in experimental conditions. Hence, the IVI of the OZURDEX implant in humans could be performed in a smoother manner.…”
Section: Discussionmentioning
confidence: 97%
“…However, the device presented here is envisioned for intravitreal implantation via syringe, similar to the Ozurdex device that is implanted with a custom injector with an outer diameter equivalent to a 22‐gauge needle . As was seen in the case of Ozurdex, an augmented or custom injector needle is likely preferred and perhaps necessary for this class of devices.…”
Section: Discussionmentioning
confidence: 99%
“…The previous DDS needle required a high penetration force and had a prolonged friction phase while insertion as compared to the modified sharper 22-G DDS applicator which achieves less resistance to the sclera even with low piercing and cutting forces and with a chevron-shaped incision, thus ensuring a proper wound closure even in vitrectomized eyes. [ 10 ] This adverse event occurred with the previous, less refined DDS applicator.…”
Section: Discussionmentioning
confidence: 99%